2018
DOI: 10.3892/etm.2018.6250
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl-2 and Bad in hippocampus of status epileptic rats and molecular mechanism of intervened recombinant human erythropoietin

Abstract: Injury of hippocampal neurons in status epilepticus (SE) SD rats kindled by pentylenetetrazol (PTZ) were studied, and the changes of apoptosis neurons, protein expression of Bad and Bcl-2 alone and combined application of phosphatidyl inositol 3-kinase (PI3K) inhibitor LY294002 and recombinant human erythropoietin (rHuEpo) were evaluated for the possible mechanisms of rHuEpo. The SE rats kindled by the PTZ were randomly divided into normal control group [normal saline (NS)], model group (PTZ + NS), rHuEpo trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…TUNEL staining directly detects apoptotic cells, and the Bcl-2 protein family regulates apoptosis by controlling the release of mitochondrial apoptosis factors, cytochrome c, and apoptosis induction factors, which activate downstream executive reactions, including caspases (Zamzami and Kroemer, 2001). Previous studies demonstrated that caspase-3 was significantly activated in the brain of rats with epilepsy, cleaved caspase-3 significantly increased, the pro-apoptotic protein Bax increased, and the anti-apoptotic protein Bcl-2 decreased (Akcali et al, 2005; Yu et al, 2018). Our results confirmed these changes, and AST reversed these changes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TUNEL staining directly detects apoptotic cells, and the Bcl-2 protein family regulates apoptosis by controlling the release of mitochondrial apoptosis factors, cytochrome c, and apoptosis induction factors, which activate downstream executive reactions, including caspases (Zamzami and Kroemer, 2001). Previous studies demonstrated that caspase-3 was significantly activated in the brain of rats with epilepsy, cleaved caspase-3 significantly increased, the pro-apoptotic protein Bax increased, and the anti-apoptotic protein Bcl-2 decreased (Akcali et al, 2005; Yu et al, 2018). Our results confirmed these changes, and AST reversed these changes.…”
Section: Discussionmentioning
confidence: 97%
“…However, the underlying molecular mechanisms are yet completely understood. Previous studies reported that the neuronal death in the brain after SE mainly includes apoptosis and necrosis, and apoptosis is an important factor (Yu et al, 2018). Our study showed that neuronal apoptosis in the hippocampal CA1 region was obvious in SE rats using TUNEL staining, which is consistent with previous studies (Kotloski et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Активация эритропоэтином Akt и PI3K была подтверждена в ряде исследований [15,[32][33][34][35][36]. Дополнительно, путем стимуляции PI3K, эритропоэтин демонстрировал противовоспалительный эффект [37].…”
Section: экспериментальные данные о кардиопротекторном эффекте эритро...unclassified